The Informative And Communicative Distance In Designing Logos Of Iraqi Ministries (Al-Academy, 2024)
The current research deals with the informative and communicative dimension in studying the nature of the sign, the most important classifications dealt with by the linguistic and non-linguistic sign and its effectiveness in contemporary graphic philosophical thought, and its role in guiding the mechanisms of visual and communicative work, and the role of the sign in particular with the slogans of some Iraqi ministries. The research contained four chapters that included the first The research problem, its importance, and the need for it, so the current research problem identified what is the informative and communicative dimension in designing the logos of the Iraqi ministries, according to a semiotic reading of the nature of the sign, its communicative role, and deciphering its symbols and codes. As for the limits of the research included in the first chapter, it was limited to studying the logos of some Iraqi ministries, while the second chapter included the theoretical framework, dealing with the first topic (the concept of the mark in the design, the dimensions of the mark in the design of the logo, the reduction in the design of the logo, the intensification in the design of the logo). And the second topic (communication in design, elements of the communication process). The third chapter concerned the procedures that included the research community, the slogans of some Iraqi ministries, and the fourth chapter included the most important results and conclusions.